Hydraulic and Sediment Transport Simulation of Koiliaris River Using the MIKE 21C Model. (2016) - Morianou, Giasemi G.; Kourgialas, Nektarios N.; Karatzas, George P.; Nikolaidis, Nikolaos P.
Abstract: The objective of this work is the simulation of the water depth, flow velocity and sediment transport in the downstream part of the Koiliaris River (Crete – Greece). The two-dimensional hydraulic model MIKE 21C is used, which has been developed specifically to simulate 2D flows and morphological changes in rivers. The model is based on an orthogonal curvilinear grid and comprises two parts: (a) the hydrodynamic part which is based on the Saint-Venant equations and (b) the morphological change part for the sediment transport. The curvilinear grid and bathymetry files were generated using a very high resolution DEM (1 m x 1 m). Time series discharge data from a hydrometric station and a 2D map of initial surface water elevation were also introduced as input parameters in the hydrodynamic part of the model. Regarding the sediment transport model, field measurements of the sediment characteristics and the suspended sediment concentration were used. The model was calibrated and verified using water level field data and sediment concentration data that were collected during high and low flow discharges. Model simulation was in good agreement with field observations as indicated by a variety of statistical measures. The results of the model were 2D maps of flow velocity, water depth, sediment transport and bed level changes. Using the obtained simulation results, extreme hydrological events such as droughts or floods transporting large sediment loads, can be monitored in the study area.